Analysis of the degree of environmental impact during the construction of the tourist and recreational complex Elbrus - Sasikova Natalya; Khadzhidi Anna; Samartseva Aleksandra; Kravchenko Lyudmila; Belts Aleksey (E3S Web of Conferences)
The analysis of the degree of environmental impact as a result of the construction and operation of the projected tourist infrastructure facilities on the territory of the all-season tourist and recreational complex Elbrus consists in the urgent need to control the anthropogenic impact as a result of the active development of the tourism industry in the territory of the National Park Prielbrusye in the areas of recreational use and educational tourism.